Development of a System for Testing Grid-connected Doubly Fed Induction Generators with Implementation of a Three-level Neutral-Point-clamped Converter - Hu, Xiao Ming (Department of Electrical Engineering, 2019)
Consistent international efforts have been made over the past few decades to move the world towards an environmentally sustainable society. Wind energy conversion systems (WECSs) are one of the largest contributors within this movement. Furthermore amongst existing wind turbine power generation technologies, the doubly fed induction generator (DFIG) has been distinctively popular for its lower capital costs especially in higher power applications. In order to study the integration of this type of generator into the grid, a laboratory based DFIG test rig was developed where its complete design process is presented in this dissertation. Mathematical modelling of related system components were thoroughly investigated so as to facilitate controller design based on the internal model control (IMC) methodology. In addition, a complete soft grid synchronisation procedure for the DFIG was investigated. It was found that the application of active damping within the IMC control law resulted in reduced stator current transients during synchronisation. Control voltage excitation for the DFIG rotor circuit was achieved by the implementation of two voltage source converters (VSC’s) connected in a back-to-back configuration via a common DC-link. The rotorside converter (RSC) was responsible for regulating the machine speed whereas the grid-side converter (GSC) was responsible for regulating the DC-link voltage. In addition, these converters provided decoupled and bidirectional power flow control which enabled the DFIG to operate at sub synchronous and super synchronous speeds. A three-level VSC was chosen for the GSC control, where a resource conservative modulation algorithm that eliminates DC-link neutral voltage unbalance was implemented. The DFIG system design was simulated, and the results were verified through experimental tests performed on a 1.5kW wound rotor induction machine (WRIM). A detailed description of the laboratory setup of the DFIG is presented, and various practical limitations are discussed. It was found that the performance of the developed DFIG test rig correlated well with results of the simulations. Stable operation was achieved for various system test conditions, which indicated the system’s robustness to serve as a practical platform for future DFIG related research.